MODERN METHODS OF TEACHING KAZAKH LANGUAGE IN SCHOOL EDUCATION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
This article analyzes advanced methods used in teaching the Kazakhlanguage in general education schools based on modern educational requirements.The main focus is on the practical effectiveness of such methods as thecommunicative approach, CLIL technology, digital tools, and gamification. Duringthe study, an increase in students' interest and active participation in languagelearning was observed. The article also presents existing problems andrecommendations for their elimination.